Declines in native forb richness of an imperiled plant community across an anthropogenic nitrogen deposition gradient. Issue 2 (5th February 2020) - Valliere, Justin M.; Bucciarelli, Gary M.; Bytnerowicz, Andrzej; Fenn, Mark E.; Irvine, Irina C.; Johnson, Robert F.; Allen, Edith B.
Abstract: Anthropogenic nitrogen (N) deposition is known to reduce plant diversity in ecosystems worldwide; however, effects on the diversity of Mediterranean‐type ecosystems—global hotspots of biodiversity—are relatively unexplored. In California, elevated N deposition due to air pollution has a multitude of ecological effects including the facilitation of nonnative plant invasion and altered ecosystem functioning, but impacts on plant richness have been inadequately quantified. We addressed this research gap by evaluating patterns of plant richness in coastal sage scrub (CSS), a severely threatened, highly diverse Mediterranean‐type shrubland, across the Santa Monica Mountains National Recreation Area. This is the largest urban national park in the United States and experiences a strong gradient of N deposition due to its proximity to urban Los Angeles. We measured soil N, plant cover, and richness at 30 CSS sites across this gradient and used regression analyses to explore relationships between richness, N deposition, and other environmental variables. We observed significant declines in plant richness across a steep gradient of soil N availability that paralleled patterns of N deposition, primarily due to decreases in native forb species. Our analyses identified soil N as the best predictor of patterns of native forb richness, but other factors, including nonnative plant cover and aridity, may also drive reduced richness. In addition to the marked decline in the number of native forb species, increasing N deposition was also associated with lower native shrub richness per area and increased cover of nonnatives. These results highlight the threat posed by N deposition to the conservation of this already imperiled ecosystem under continued environmental change.